PRECAUTIONS TAKEN DURING PRESCRIPTION OF RASA AUSHADHA (HERBO-MINERAL DRUGS) - Wijayanthamala, M.V.R.; Kaur, Harpreet; Kumar, Harish; Sanjay, Kumar (International Journal of Ayurveda and Pharma Research, 2015)
Rasa Shastra is a very super specialist field in the Ayurvedic sector. Rasa Aushadha also has provided efficacious and effectual results for Sadya, Kricha Sadya, Yapya and even Asadya Roga conditions. But treat with Rasa Aushadha to a patient like eating curd with the help of sharp knife. That means all Rasa Aushadhas which are formulated without adopting standard operative procedure mention in the Rasacharyas in their treaties, without proper diagnose of disease condition, without well planned treatment plan, Prescribing Rasa Aushadha ignoring Rogabala, Rogibala, Aushadhamatra, treatment duration, proper Anupana, Contra indications, other drug interactions, Patya Pathya, without qualified physicians supervision, irregular clinic visit, insufficient advise to patients etc., that medicine totally same as poison to a patient. Hence there are so many factors behind the Cikitsa with Rasa Aushadha which should be taken into interest. The physician who are utilizing Rasa Aushadha for alleviate any disease conditions they should be taken responsibility to serve to patients more benefit and very less or no harm. Every Ayurvedic classics has been written clearly even before two thousand years ago essential features of Vaidyadi Chatushpada those are directly related with ethical and moral issues and Rasa Granthas specially mention the same. According to Rasa Vaidhyas engagement of the treatment using Rasa Aushadha that is same as sitting on the pin situated in between Nectar and poison.